Fathoming Shipping Costs : An Exploration of Recent Literature, Data, and Patterns - Ardelean, Adina; Lugovskyy, Volodymyr; Skiba, Alexandre; Terner, David (World Bank, Washington, DC, 2022)
Recent academic research on maritime shipping has been affected by two factors: (i) changes in shipping technology and market structure and (ii) the explosion of new micro data sets in shipping and international trade. This paper describes this research, focusing on containerized and dry-bulk shipping and emphasizing recent trends and determinants of freight rates. The findings are presented in a systematic set of stylized facts. Some of the important and perhaps underappreciated insights include discussion of the scale effects of utilizing fuel based on vessel size over different periods and comparison of different functional forms of transportation costs: per twenty-foot equivalent, per kilo, and ad-valorem. The paper also presents several novel empirical exercises to further the insights from the existing literature. It shows that the effect of sea distance on trade costs slowly “dies" over time, but its effect on seaborne trade volumes is both significant and persistent over time. Moreover, the paper documents the presence of substantial country- and product-level heterogeneity of the impact of sea distance on international maritime freight markets.